Anopheles (Cellia) Kokhani, N. SP.(Diptera Culicidae) from Kapit, Sarawak, East Malaysia - Vythilingam, I.; Jeffery, J.; Harbach, R.E.; Chan, S.T.; Tan, C.H.; Asmad, M. (2007)
Anopheles kokhani Vythilingam, Jeffery, and Harbach, n. sp., a member of the Neomyzomyia Series of subgenus Cellia Theobald (Diptera: Culicidae) is described from females collected in Sarawak, Malaysia, during studies to identify the mosquitoes responsible for transmitting simian malaria to humans. The species is distinguished from sympatric members of the Neomyzomyia Series, including An. saungi Colless, An. stookesi Colless, An. tessellatus Theobald, and An. watsonii (Leicester), with which it shares one or more key features. The wing and legs of the new species are illustrated.